Media, independent non-executive directors and strategy disclosure by non-financial listed firms in the UAE. Issue 2 (25th November 2019) - Hassan, Mostafa Kamal; Lahyani, Fathia Elleuch
Abstract : Purpose: This study aims to investigate the effect of media coverage, negative media tone and the interaction between negative media tone and independent non-executive directors (INEDs) on strategic information disclosure (SD). Design/methodology/approach: The authors rely on media agenda-setting theory, agency theory and a panel data set of 52 UAE non-financial listed firms from 2009 to 2016. Multivariate regressions examine the effect of media coverage and negative media tone on SD and examine the moderation of INEDs on the effect of negative media tone on SD while controlling for firm size, board size, board meeting frequency, firm profitability and leverage. Findings: The results show that negative media tone has a negative effect on SD, and there is no association between media coverage and SD. The results show that INEDs are negatively associated with SD and have a negative moderating effect on the negative media tone–SD relationship. INEDs follow a conservative approach, encouraging less SD when their firms face negative media tone. Research limitations/implications: The authors measured media coverage and negative media tone by the number of news articles. In the robustness test, they use media tone score. They measured SD using an index that captures firm strategy dimensions. Though these measures are inherently subjective, they were used to measure variation in media coverage, media tone and SD across listed UAE non-financial firms. Mitigation of subjectivity was achieved through rigorous cross-checking measurements. Practical implications: Findings assist UAE policymakers and the international business community with insights related to articulation of media to SD and INEDs' role in moderating the effect of media on SD. Originality/value: To the authors' knowledge, this is the first study that combines media agenda-setting theory with agency theory and SD in an emerging market economy (the UAE). The study is also among the few studies that illustrate the possible role of INEDs under different media tones in emerging markets.